An integrated pathway based on in vitro data for the human hazard assessment of nanomaterials. (April 2020) - Romeo, Daina; Salieri, Beatrice; Hischier, Roland; Nowack, Bernd; Wick, Peter
Graphical abstract: Highlights: Reduction of in vivo data limits nanoparticles assessment by risk methodologies. A combination of in vitro data and in silico models is proposed. In silico models are evaluated for their implementability with available data. Recommendations for the use of in vitro data in risk methodologies are provided. Abstract: In line with the 3R concept, nanotoxicology is shifting from a phenomenological to a mechanistic approach based on in vitro and in silico methods, with a consequent reduction in animal testing. Risk Assessment (RA) and Life Cycle Assessment (LCA) methodologies, which traditionally rely on in vivo toxicity studies, will not be able to keep up with the pace of development of new nanomaterials unless they adapt to use this new type of data. While tools and models are already available and show a great potential for future use in RA and LCA, currently none is able alone to quantitatively assess human hazards (i.e. calculate chronic NOAEL or ED 50 values). By highlighting which models and approaches can be used in a quantitative way with the available knowledge and data, we propose an integrated pathway for the use of in vitro data in RA and LCA. Starting with the characterization of nanoparticles' properties, the pathway then investigates how to select relevant in vitro human data, and how to bridge in vitro dose-response relationships to in vivo effects. If verified, this approach would allow RA and LCA to stir up the development of nanotoxicology by giving indications about the data and quality requirements needed in risk methodologies.